ISLAMIZATION, PIETY, FUNDAMENTALISM: RELIGIOUS MOVEMENT IN CAMPUS - Lukis Alam (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
Religion is based on the perspective of attitudes and attention to the doctrines that apply in everyday life. On its journey, diversity is often a symbol and goal of achieving certain interests. However, sometimes he often raises conflicts within the structure of society. Power and religion sometimes cannot be united, which results in friction between the authorities and their people. In this regard, the existence of this study wants to highlight the dynamics of intellectual diversity in public space. They want to fight for religious rights that have been ruled out by the government. So that with the metamorphosed Tarbiyah movement being campus preaching, they have directed a non-confrontational movement that fights Islam in the public space by taking mosque settings as the foundation of religious idealism in the modern era. The rise of campus preaching in various universities throughout Indonesia originated from the concerns of Islamic activists on the impartiality of the authorities in a system based on religious guidance. Especially in the era of the 70s when the New Order replaced the Old Order, many actions were contrary to Islamic norms. The further development of the preaching of this campus is growing rapidly, as a result there is a new Islamic model conducted by students who try to instill an ethical system to the community. This study uses a qualitative method that combines literature sources with a phenomenological approach that refers to field data. Therefore the final result of this study presents the religious aspirations of young intellectuals in their relations with the political interests of the ruler who display modern piety attitudes that process into contemporary Islamic models in the public sphere. Keberagamaan didasarkan pada perspektif sikap dan atensi atas doktrin yang berlaku di dalam kehidupan sehari-hari. Pada perjalanannya, keberagamaan seringkali menjadi simbol dan tujuan mencapai kepentingan tertentu. Namun, adakalanya ia kerap memunculkan pertentangan di dalam struktur masyarakat. Kekuasaan dan agama terkadang tidak bisa disatukan, yang berakibat pada gesekan antara penguasa dengan rakyatnya. Berkaitan dengan hal tersebut, adanya penelitian ini ingin menyoroti dinamika keberagamaan kaum intelektual di ruang publik. Mereka ingin memperjuangkan keberagamaan yang selama ini dikesampingkan penguasa. Sehingga dengan gerakan Tarbiyah yang bermetamorfosa menjadi dakwah kampus, mereka telah mengarahkan pada suatu gerakan non-konfrontatif yang memperjuangkan Islam di ruang publik dengan mengambil setting masjid sebagai landasan idealisme keberagamaan di era modern. Maraknya dakwah kampus di berbagai universitas di seluruh Indonesia berawal dari keprihatinan para aktivis Islam terhadap keberpihakan penguasa pada liberalisasi nilai dan moral. Terlebih di era 70-an saat Orde Baru menggantikan Orde Lama, banyak sekali tindakan-tindakan yang bertentangan dengan norma Islam. Perkembangan selanjutnya, dakwah kampus ini berkembang dengan pesat, akibatnya terjadi model keislaman baru yang dilakukan oleh mahasiswa yang mencoba menanamkan sistem etika kepada masyarakat. Penelitian ini menggunakan metode kualitatif yang memadukan sumber-sumber pustaka dengan pendekatan fenomenologis yang mengacu dari data lapangan. Oleh karena itu, hasil akhir penelitian ini menyuguhkan aspirasi keberagamaan kaum intelektual muda dalam persinggungannya dengan kepentingan politik penguasa yang menampilkan sikap-sikap kesalehan modern yang berproses menjadi model Islamisasi kontemporer di ruang publik.